Mathematical Relationship between Temperature Change and the Changing Consumption of the Product and Kerosene Consumption Forecasting for these years (2005-2015) (Baghdad Science Journal, 2009)
The aim of this study is to construct a Mathematical model connecting the variation between the ambient temperatures and the level of consumption of kerosene in Iraq during the period (1985-1995), and use it to predict the level of this consumption during the years (2005-2015) based on the estimation of the ambient temperatures.